Experimental and numerical analysis of epoxy based adhesive failure on mono- and bi-material single lap joints under different displacement rates - Hojjat Ghahramanzadeh Asl; Salim am; Osman Orhan; Adnan zel (Fracture and Structural Integrity)
Development in material science imposes to use different materials in production. This causes a problem for joining different materials because traditional joining techniques such as welding could not overcome this problem in industries such as automotive. Hence, adhesive bonding overcomes this problem by its superiorities to join different materials. The joint strength of epoxy-based adhesives is affected by adhesive thickness, adherents surface quality, and curing conditions. In this study, two different materials (SAE 304 and AL7075) were bonded by epoxy adhesive (3M DP460NS) as single lap joint (SLJ) of Aluminum-Aluminum, Steel-Steel, and Aluminum-Steel. The effects of adhesive thickness (0.05, 0.13, 0.25 mm) and surface roughness (281, 193, 81 nm) to strength were compared. SLJs were tested for 1, 10, 25 and 50 mm/min displacement rates. Adhesive surface structures were imaged by Scanning Electron Microscopy (SEM) to investigate adhesive fractures. Surface roughnesses were examined by using Atomic Force Microscopy (AFM) to compare its influence on failure load. Finite Element Analysis (FEA) was conducted by using Cohesive Zone Model with ANSYS 18.0 software to obtain stress distribution of adhesive. Optimum values according to the present conditions of the thickness (0.13mm) and roughness (minus 200nm) were determined. Experimental results were demonstrated that while displacement rates rose, failure loads increased as well. FEA analysis was fit to experimental results. It has been observed that along with material type, peel stresses become an important factor for joint strength.